Possibilities of Creating Multifunction Sensors Based on Auto-Oscillating Current in Silicon - Kh.U. Kamalov; G.S. Nurimbetova; T.U. Kamalov; R.M.Asetullaeva; D.G.Bekchanov (Zien Journals, 2022)
This paper demonstrates the possibility of manufacturing multifunction sensors based on the influence of external factors on the auto-oscillating current parameters in a nanocluster silicon material consisting of a margens atom
Keywords: nanocluster; silicon; multi-charged center; current self-oscillations